Effects of climate and land use changes on water ecosystem services: understanding the mitigating effect of green land use scenarios - Anjinho, Phelipe da Silva (2024)
Water ecosystem services (WES) are crucial for preserving environmental quality and human well-being. Their degradation is primarily associated with climate and land use changes. This study aimed to understand how these factors affect WES in the Jacaré-Guaçu river basin, located in São Paulo, Brazil. Regional climate and biophysical models were used to investigate the effects of different climate and land use scenarios on erosion control, water supply, and purification services. Indicators such as sediment export and retention (erosion control), total nitrogen and total phosphorus export and retention (water purification), and quickflow and baseflow (water provision) were used to quantify these services. The research hypothesis involved testing whether green land use scenarios, based on increasing native vegetation, could enhance provision and mitigate adverse effects of climate change on WES. The research was structured into six chapters, with the first chapter presenting the general introduction, objectives, and research hypothesis. The second chapter involved a literature review on WES, aiming to identify potentials, limitations, and gaps in applying this approach to water resources planning and management. The third chapter assessed the performance of InVEST biophysical models in predicting observed values of WES, discussing important issues such as sensitivity, calibration of biophysical parameters, and validation of simulations. The fourth chapter investigated the effects of past land use changes on WES, proposing environmental zoning to identify priority areas for conservation and restoration of native vegetation, and evaluating the impacts of a planned land use scenario on WES. The fifth chapter assessed the individual and combined effects of four climate scenarios (RCP 4.5 2040-2069, RCP 4.5 2070-2099, RCP 8.5 2040-2069, RCP 8.5 2070-2099) and three land use scenarios (economic, trend, and green) on WES. Additionally, in the fifth chapter, the overall hypothesis of the research was tested. The results of all studies allowed understanding the individual and combined effects of climate and land use changes on WES, highlighting the positive effects of green land use scenarios on the provisioning of WES and mitigation of climate change impacts. The contributions and insights of this research are important for researchers and public managers interested in integrated planning and management of water resources.